2018
DOI: 10.1039/c8bm00263k
|View full text |Cite
|
Sign up to set email alerts
|

Systemic delivery of CRISPR/Cas9 with PEG-PLGA nanoparticles for chronic myeloid leukemia targeted therapy

Abstract: Chronic myeloid leukemia (CML), which is characterized by the Philadelphia translocation, which fuses breakpoint cluster region (BCR) sequences from chromosome 22 upstream of the Abelson murine leukemia viral oncogene homolog (ABL) on chromosome 9, requires specific and efficient treatment. The CRISPR/Cas9 system, with its mechanism of specific DNA complementary recognition by engineered guide RNA (gRNA), allows the development of novel therapeutics for CML. To achieve targeted therapy of CML with the CRISPR/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 37 publications
0
48
0
Order By: Relevance
“…Mice that were i.v. injected with the nanocarrier showed a reduced number of myelogenous leukemia cells (K562) in blood and bone marrow and a significant prolonged survival rate after the treatment compared to naive and vehicle controls ( Liu et al, 2018 ).…”
Section: Combination Treatments With Plga Npsmentioning
confidence: 99%
“…Mice that were i.v. injected with the nanocarrier showed a reduced number of myelogenous leukemia cells (K562) in blood and bone marrow and a significant prolonged survival rate after the treatment compared to naive and vehicle controls ( Liu et al, 2018 ).…”
Section: Combination Treatments With Plga Npsmentioning
confidence: 99%
“…In order to address these challenges, transient delivery of sgRNA along with the Cas9 mRNA or Cas9 protein has been achieved using non-viral methods such as electroporation, 15,16 hydrodynamic injection, 17 microinjection, 18 lipids, [19][20][21][22] peptides, [23][24][25][26][27][28] polyethylenimine in combination with other agents such as DNA nanoclew, graphene oxide, cholesterol, [29][30][31] gold nanoparticles and other nanostructures, [32][33][34][35][36][37][38] extracellular vesicles, [39][40][41][42] virus-like particles, 43 and biolistic delivery in plants. 44,45 Apart from these methods, many hybrid frameworks have also been used to deliver CRISPR/Cas9.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, in a study by GarcĂ­a-Tuñón et al , it was observed that CRISPR Cas9 was able to effectively control the oncogenic capabilities of BCR-ABL chimeric gene in custom Boff-p210 cell line carrying BCR-ABL fusion transgene 9 . In a recent study, Liu et al demonstrated effective down regulation of BCR-ABL gene using CRISPR RNA guided Fokl Nucleases in both cell lines and murine xenograft model 30 . However, GarcĂ­a-Tuñón et al , in their other research article on CRISPR, published recently, highlighted the limitation of CRISPR/Cas9 in effectively knocking out target DNA without a null variation inducing homology directed repair template in the construct.…”
Section: Discussionmentioning
confidence: 99%